Interprofessional Collaboration and Education in the Hierarchical and Collectivistic Culture - Susilo, Astrid Pratidina; Riskiyana, Rilani; Lestari, Endang; Yanti, Yanti (Springer Singapore, 2022)
The socio-hierarchical gaps were also prominent in communication and collaboration among health professionals in the hierarchical and collectivistic culture. As a result, it is highly challenging to initiate two-way dialogues between health professionals. Health professionals are not always ready to assume their advocacy roles in collaboration to guard the safety of the patients. This chapter will discuss the importance of interprofessional collaboration to promote patient safety, the influence of hierarchical and collectivistic context, and the root of stereotyping. We will also discuss that the history of each profession also played a role in shaping the stereo-types. At the end of this chapter, we provide some educational models from the hierar-chical and communal context to improve interprofessional collaboration. The examples are from different education contexts (e.g., PBL, skills training, community-based education) to help readers grasp principles on designing interprofessional education in a hierarchical and communal context.